Promosi Potensi Dan Produk UMKM Menggunakan Metode Rapid Application Development Berbasis Web - Puspa, Misrawati Aprilyana; Hariati Husain; Ariska Julaeha Tangkudung (JSAI (Journal Scientific and Applied Informatics), 2024)
The potential of a village encompasses various aspects that can be developed to improve the welfare of the community, including natural resources, economy, society, and infrastructure. Tanjung Kramat Village has significant potential in the field of Micro, Small, and Medium Enterprises (MSMEs), especially tuna-based processed products such as shredded tuna, tuna meatballs, crackers, sausages, dumplings, and pempek. Although these products are affordable, the main challenges are the conventional promotion and distribution methods, as well as limited access to technology. Most promotions remain local and have not optimally utilized digital technology, hindering local economic growth. Based on interviews, 75% of Tanjung Kramat Village residents work as fishermen and rely on the processing of fishery products. Therefore, a technology-based solution is needed to facilitate broader marketing. This study aims to design a digital application that assists MSME product owners in Tanjung Kramat Village in promoting and selling their products across Indonesia. The Rapid Application Development (RAD) method will be applied, involving users actively to ensure the application meets their needs. This research is relevant and important, as the designed application will serve as a digital tool for the community to expand markets and increase income, thereby positioning MSMEs as a driving force for the local economy